Rural-urban differences in meeting physical activity recommendations and health status in cancer survivors in central Pennsylvania - Mama, Scherezade K.; Bhuiyan, Nishat; Foo, Wayne; Segel, Joel E.; Bluethmann, Shirley M.; Winkels, Renate M.; Wiskemann, Joachim; Calo, William A.; Lengerich, Eugene J.; Schmitz, Kathryn H. (Supportive care in cancer, 2020)
Purpose This study explored rural-urban differences in meeting physical activity (PA) recommendations and health status in cancer survivors in central Pennsylvania and associations between PA and health status. Methods Cancer survivors ( N = 2463) were identified through a state cancer registry and mailed questionnaires assessing PA and health status. Rural-urban residence was based on county of residence at diagnosis. Participants self-reported frequency and duration of leisure-time PA and were classified as meeting: (1) aerobic recommendations (≥ 150 min/week), (2) muscle-strengthening recommendations (≥ 2 times/week), (3) both aerobic and muscle-strengthening recommendations, or (4) neither recommendation. Logistic regression models examined associations between rural-urban residence and meeting PA recommendations and associations between PA and health status, adjusting for age, cancer type, gender, and income. Results Nearly 600 ( N = 591, 24.0%) cancer survivors returned completed questionnaires (rural 9.5%, urban 90.5%). Half (50.0%) of rural cancer survivors reported no leisure-time PA compared to 35.2% of urban cancer survivors ( p = 0.020), and urban cancer survivors were 2.6 times more likely to meet aerobic PA recommendations (95% CI 1.1–6.4). Odds of reporting good physical and mental health were 2.3 times higher among survivors who reported meeting aerobic recommendations compared to those who did not meet PA recommendations (95% CI 1.1–4.5), adjusting for rurality and covariates. Conclusions Results demonstrate persistent rural-urban differences in meeting PA recommendations in cancer survivors and its association with self-reported health. Implications for cancer survivors Findings underscore the need for interventions to increase PA in rural cancer survivors in an effort to improve health status and reduce cancer health disparities.